2018
DOI: 10.1016/j.molcel.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A Liquid to Solid Phase Transition Underlying Pathological Huntingtin Exon1 Aggregation

Abstract: SummaryHuntington’s disease is caused by an abnormally long polyglutamine tract in the huntingtin protein. This leads to the generation and deposition of N-terminal exon1 fragments of the protein in intracellular aggregates. We combined electron tomography and quantitative fluorescence microscopy to analyze the structural and material properties of huntingtin exon1 assemblies in mammalian cells, in yeast, and in vitro. We found that huntingtin exon1 proteins can form reversible liquid-like assemblies, a proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
285
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(308 citation statements)
references
References 81 publications
21
285
1
1
Order By: Relevance
“…This approach could be extended to image young Q40 nematodes in larval stages at higher resolution, to find out if similar non-amyloid inclusions comprised of e.g. oligomeric 28 or liquid-like states 37 are visible as precursors in this system. For the longitudinal studies described here, we were able to perform the complete set of experiments in less than 2.5 h for each day of measurement (ca.…”
Section: Resultsmentioning
confidence: 99%
“…This approach could be extended to image young Q40 nematodes in larval stages at higher resolution, to find out if similar non-amyloid inclusions comprised of e.g. oligomeric 28 or liquid-like states 37 are visible as precursors in this system. For the longitudinal studies described here, we were able to perform the complete set of experiments in less than 2.5 h for each day of measurement (ca.…”
Section: Resultsmentioning
confidence: 99%
“…While we know well how cells guard the structure of stably folded proteins [123][124][125][126][127], we know virtually nothing about the mechanisms that guard IDPs. IDPs, including IDPs related to degenerative diseases such as Huntington's disease and amyloid lateral sclerosis, and FG-Nups, can phase separate to form liquid-liquid demixed droplets [128] or hydrogels [129][130][131] or aggregate to form amyloid fibers [64][65][66][132][133][134][135][136].…”
Section: Maintenance Quiescent Muscle Cells Maintain Theirmentioning
confidence: 99%
“…Relatively dry environments where phenomena equivalent to this can occur include the core of globular proteins 44 , the interior of cell membranes 45 , as well as amyloid fibrils, where hydrogen bonding interactions involving Gln and Asn side chains parallel to the fibril axis contribute to the stability of the quaternary structure 46 . In addition, it has been shown that both exon 1 of huntingtin 47 and the transactivation domain of the AR 48 form condensates that define environments of low dielectric constant, where electrostatic interactions may be strongly favored 49 . It will be interesting to address whether this phenomenon plays a role in the highly cooperative liquidliquid phase separation process of these and similar proteins, as has been proposed to be the case for protein folding, where considering the contextdependent strength of interresidue interactions proved important for reproducing the high cooperativity of protein folding in lattice simulations 50 .…”
Section: Discussionmentioning
confidence: 99%